PENERAPAN TIPOLOGI PASAR, ARSITEKTUR DAN PERILAKU GENERASI Z PADA PERANCANGAN PASAR MASA DEPAN DI GONDANGDIA - Irwin Irwin; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The pandemic caused by the corona virus has changed the lifestyle of humans, both directly and indirectly, especially generation Z in Jakarta. The way humans meet their primary needs also changes over time. Many of generation Z decide to shop online to meet their individual needs. Generation Z defines balance as one of the things that is seen in living life, including meeting their needs and interacting with others. The Future Market in Gondangdia exists as a forum that provides space for buying and selling transactions to be more interactive, creative, flexible, and in accordance with health protocols. Through dis-programming, combining creative buying and selling programs and public space as one unit in a design is one of the methods used in designing architectural programs. The combination of the two programs creates an equal space with alternate uses depending on time. The emerging market typology method and its relation to Z generation architecture and behavior become a design strategy in designing. This provides an innovative and interactive buying and selling space according to the needs of generation Z. Keywords: Buy and sell spaces; Public spaces; Future markets; Generation Z; Buy and sell; Dis-programming AbstrakPandemi yang disebabkan oleh virus korona telah mengubah gaya hidup manusia, baik secara langsung maupun tidak langsung, khususnya generasi Z di Jakarta. Cara manusia dalam memenuhi kebutuhan primernya pun berubah seiring berjalannya waktu. Banyak dari generasi Z memutuskan untuk berbelanja online untuk memenuhi kebutuhannya masing-masing. Generasi Z mendefinisikan keseimbangan sebagai salah satu hal yang dilihat dalam menjalani kehiduoan termasuk dalam memenuhi kebutuhannya dan berinteraksi dengan sesamanya. Melalui dis-programming memadukan program jual beli kreatif dan ruang publik sebagai satu kesatuan di dalam sebuah desain merupakan salah satu metodw yang digunakan dalam perancangan program arsitektur. Perpaduan kedua program tersebut menciptakan sebuah ruang yang sama dengan penggunaanya bergantian tergantung oleh waktu. Metode tipologi pasar yang berkembang dan kaitannya dengan arsitektur dan perilaku generasi Z menjadi strategi desain dalam merancang. Hal ini memberikan ruang jual beli yang inovatif dan interaktif sesuai dengan kebutuhan generasi Z.